2014
DOI: 10.1007/s00261-014-0308-5
|View full text |Cite
|
Sign up to set email alerts
|

CT evaluation of common duct dilation after cholecystectomy and with advancing age

Abstract: Remote cholecystectomy patients have larger CD diameters than the nonoperated and interval cholecystectomy groups. Greater increase in ductal diameter occurred between studies in the interval cholecystectomy patients, suggesting that dilation occurs after cholecystectomy. Also, the CD dilates slightly with age in nonoperated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
0
25
0
1
Order By: Relevance
“…The CBD diameter did not significantly increase between the third and the sixth month, so we can conclude that the CBD was maximally dilatated three months after cholecystectomy. Many other studies also found post-cholecystectomy CBD dilatation ( 4 , 7 - 9 , 34 - 37 ). Most of these studies measured the CBD at 1-3 points, whereas our study used 8 measurement points.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The CBD diameter did not significantly increase between the third and the sixth month, so we can conclude that the CBD was maximally dilatated three months after cholecystectomy. Many other studies also found post-cholecystectomy CBD dilatation ( 4 , 7 - 9 , 34 - 37 ). Most of these studies measured the CBD at 1-3 points, whereas our study used 8 measurement points.…”
Section: Discussionmentioning
confidence: 72%
“…ERCP may show a larger CBD diameter due to increased pressures caused by the contrast medium injection in the CBD ( 28 , 29 ). CT measurements may be slightly larger (by 1.7 mm) than the US measurements because CT measurements are performed outer wall-outer wall, while US measurements are performed inner wall-inner wall ( 30 , 31 ). Most of the techniques (such as US and CT) cannot image the cystic duct because it is too small, so special care must be taken not to include the cystic duct in the CBD measurement ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gallstones are known to be closely related to biliary inflammation. [ 31 ] A highly significant increase in bile duct diameter and bile duct pressure was demonstrated after cholecystectomy which accounts for subsequent chronic inflammation. [ 32 ] Furthermore, the post-cholecystectomy bile duct dilatation increases with time, leading to greater severity of biliary inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, dilation in the common bile duct is sometimes observed after cholecystectomy with no known negative consequences. 35, 36…”
Section: Resultsmentioning
confidence: 99%